Iraqi Super Grid Network State Estimation Using PSO Technique - Abood, Assist. Prof. Dr. Afaneen A.; Hameed, Anmar Jasim (University of Thi-Qar Journal, 2019)
Power System State Estimation (PSSE) became a main subject in the operation of power systems through its important role in ensuring the secure and economical operation of the power system. In this work, two approaches were proposed and implemented in order to search for the optimal solution of state estimation in power systems, the first approach used a conventional state estimation program based on Weighted Least Square (WLS) method, and the second one used an intelligent technique based on Particle Swarm Optimization (PSO). All programs were implemented using MATLAB and developed to solve the state estimation problem of the Iraqi Super Grid network (400kV). The results showed that the PSO is more accurate and it convergence close to the optimal solution